THE IMPACTS OF LEARNING TO READ ON BRAIN ACTIVITY AND A SOCIOCULTURAL VIEW ON HUMAN COGNITIVE FUNCTIONING: A POSSIBLE RELATION - Agnoletto, Matheus André; Tomitch, Lêda Maria Braga (Revista Educação e Linguagens, 2021)
Abstract: the present paper has a threefold objective: (i) to present a sociocultural view on human mental functioning; (ii) to review studies on the impacts of learning to read on brain activity; and (iii) to draw a parallel between a vygotskian view on human cognition and neuroscientific evidence of how learning to read impacts brain activity. The studies reviewed show the ways reading acquisition results in changes in brain activity, as well as how the brain reorganizes itself in order to accommodate new functions as a response to this process. From a vygotskian instance, this illustrates how one’s cognitive development is fostered on the external plane as they interact with socioculturally constructed means.